Unsaturated dietary fat increases egg size - A mechanism - Moudgal, R P (The Indian Journal of Animal Sciences, 2012)
Unsaturated dietary fat (sunflower oil) improves egg weight, deserves further elucidation of the possible but still unknown mechanism. Two isocaloric and isonitrogenous dietary regimens with or without 9% sunflower oil were fed to WL layers. On laparotomy, the preovulatory follicles (Fâ‚) from both of the groups were similar in weight but the moisture in the yolk of ovarian follicle obtained from sunflower oil fed group was significantly (P<0.05) lower than that of control. In vitro study across the follicular wall indicated that this difference might be because of relatively higher transport rate of moisture in control group compared to sunflower oil fed group. In turns, it may be possible that the yolk of developing egg in oviduct of sunflower fed group may be receiving more water because of higher osmolarity difference compared to control group. The existence of this phenomenon find support in the observation wherein the presence of significant (P<0.05) difference in moisture content of yolk at ovarian follicle level (Fâ‚) between these 2 groups narrowed down to non-significant level in the yolk of freshly laid eggs.